Digital Technology in Senior Entrepreneurship: A Qualitative Study - Loo, Bee Hou; Tan, Yun Yi; Hong, Meenchee (Journal of Entrepreneurship, Business and Economics, 2024)
The global population aged 65 and over is approaching 800 million and is expected to represent 16% of the total population by 2025. Many countries are experiencing demographic shifts towards an older population, resulting in a declining ratio of working-age individuals. The rapid increase in the elderly population raises concerns about healthcare and financial burdens on nations. One potential solution to these challenges is senior entrepreneurship, which allows older adults to participate in the workforce and foster social inclusion. While senior entrepreneurship has the potential to alleviate financial burdens and improve well-being, the specific factors that drive it are still unclear, especially, the adoption of digital technologies. Thus, this study investigates the impacts of digital literacy on senior entrepreneurship, and the potential of digital literacy training in stimulating business interest among seniors. The data were gathered using purposive sampling technique, respondents were selected from a digital literacy training program designed specifically for older adults. Standardised open-ended interviews were conducted with participants both before and after the training. The study reveals that over half of the respondents felt significantly motivated to start a business following the digital literacy program. Financial support from the government or other organisations was identified as a crucial factor influencing their decision, as many seniors expressed concerns about financial stability and the risks associated with starting a business. Additionally, new findings not covered in the literature review include a growing concern about digital technology security. By examining the role of digital literacy in promoting senior entrepreneurship, this study provides actionable insights for stakeholders seeking to enhance senior employment and business opportunities. Research Paper Keywords: Senior Entrepreneurship, Digital Literacy, Ageing Society, Qualitative Approach Reference to this paper should be made as follows: Loo, B.H., Tan, Y.Y., & Hong, M. (2024). Digital Technology in Senior Entrepreneurship: A Qualitative Study. Journal of Entrepreneurship, Business and Economics , 12 (1), 190–230.